IMPROVING CUSTOMER LOYALTY WARDAH BRAND THROUGH BRAND IMAGE AND PRICE FAIRNESS: CUSTOMER SATISFACTION AS AN INTERVENING VARIABLE - Junaedi, Achmad Tavip; Wijaya, Evelyn; Santoso, Pamuji Hari; Chandra, Stefani (Jurnal Aplikasi Manajemen, 2022)
This research aimed to analyze the effect of brand image and price fairness on Wardah brand customer loyalty with customer satisfaction as an intervening variable. The data used was primary data collected using a questionnaire containing 21 questions. The number of respondents was 165 respondents consisting of Customers who made repeated purchases of Wardah products in Pekanbaru City. The data were analyzed using path analysis with the help of the PLS program. The results showed that brand image and price fairness positively and significantly affected customer satisfaction. The brand image had an insignificant effect on customer loyalty. Price fairness and customer satisfaction positively and significantly affect customer loyalty. Brand image intervened by customer satisfaction had a positive and significant effect on customer loyalty. The last one is price fairness intervened by customer satisfaction had an insignificant effect on customer loyalty. Thus, companies should maintain customer satisfaction to reinforce customer loyalty and gain a larger market share.